Therapeutic intragastric vaccination against Helicobacter pylori in mice eradicates an otherwise chronic infection and confers protection against reinfection. - Ghiara, P (1997)
Chronic infection of the gastroduodenal mucosae by the gram-negative spiral bacterium Helicobacter pylori is responsible for chronic active gastritis, peptic ulcers, and gastric cancers such as adenocarcinoma and low-grade gastric B-cell lymphoma. The success of eradication by antibiotic therapy is being rapidly hampered by the increasing occurrence of antibiotic-resistant strains. An attractive alternative approach to combat this infection is represented by the therapeutic use of vaccines. In the present work, we have exploited the mouse model of persistent infection by mouse-adapted H. pylori strains that we have developed to assess the feasibility of the therapeutic use of vaccines against infection. We report that an otherwise chronic H. pylori infection in mice can be successfully eradicated by intragastric vaccination with H. pylori antigens such as recombinant VacA and CagA, which were administered together with a genetically detoxified mutant of the heat-labile enterotoxin of Escherichia coli (referred to as LTK63), in which the serine in position 63 was replaced by a lysine. Moreover, we show that therapeutic vaccination confers efficacious protection against reinfection. These results represent strong evidence of the feasibility of therapeutic use of VacA- or CagA-based vaccine formulations against H. pylori infection in an animal model and give substantial preclinical support to the application of this kind of approach in human clinical trials.